Quasi Contractions and Fixed Point Theorems in the Context of Neutrosophic Fuzzy Metric Spaces (European Journal of Pure and Applied Mathematics, 2025)
Fixed point theory has garnered significant interest due to its applicability across various scientific disciplines. In this manuscript, we present fixed point theorems pertaining to neutrosophic fuzzy quasi-contractions, situated within the sophisticated framework of neutrosophic fuzzy metric spaces. Furthermore, we establish several fixed point results pertinent to this field of research.
Keywords: Fixed point theory; Neutrosophic fuzzy metric spaces; banach contraction principle; quasi-contractions; linear contractions